3‐Arylindanones and related compounds as antiproliferative agents against colorectal cancer. (10th July 2019) - Srivastava, Ankita; Ravi, Kusumoori; Fatima, Kaneez; Maheshwari, Mayank; Ashraf, Raghib; Hasanain, Mohammad; Yadav, Pankaj; Iqbal, Hina; Kumar, Yogesh; Luqman, Suaib; Chanda, Debabrata; Khan, Feroz; et al.
Abstract: Diverse benzylidene indanones and their derivatives were synthesized as anticancer agents. Two of the analogues, that is7 and22, exhibited significant antiproliferative activity against several human cancer cell lines. Both the compounds possessed antimitotic activity and induced apoptosis in DLD1 colorectal adenocarcinoma cells through activation of caspase pathways. In cell cycle analysis, both the compounds induced predominantly G2/M phase arrest in DLD1 cells. Molecular docking studies revealed that compound7 occupies colchicine binding pocket of β‐tubulin. Both the compounds were safe in acute oral toxicity in rodents. Both the compounds are further being optimized for better efficacy. Abstract : Anticancer activity of 3‐arylindanones has been explored against colorectal adenocarcinoma.